2017
DOI: 10.1177/0143624416684641
|View full text |Cite
|
Sign up to set email alerts
|

The building performance gap: Are modellers literate?

Abstract: One of the most discussed issues in the design community is the performance gap. In this research, we investigate for the first time whether part of the gap might be caused by the modelling literacy of design teams. A total of 108 building modellers were asked to comment on the importance of obtaining and using accurate values for 21 common modelling input variables, from U-values to occupancy schedules when using dynamic simulation to estimate annual energy demand. The questioning was based on a real building… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(61 citation statements)
references
References 24 publications
1
60
0
Order By: Relevance
“…The inputs used in the LENI calculations, Eq. 1, by the external consultants in these feasibility studies were based on assumptions and best guess estimates, this is congruent with other performance gap researchers who found that consultant's thermal modelling input assumptions were highly variable (Imam et al, 2017). The operational hours can easily be replaced by actual data collected in practice.…”
Section: Comparison Across the Three Study Buildingssupporting
confidence: 81%
See 2 more Smart Citations
“…The inputs used in the LENI calculations, Eq. 1, by the external consultants in these feasibility studies were based on assumptions and best guess estimates, this is congruent with other performance gap researchers who found that consultant's thermal modelling input assumptions were highly variable (Imam et al, 2017). The operational hours can easily be replaced by actual data collected in practice.…”
Section: Comparison Across the Three Study Buildingssupporting
confidence: 81%
“…Respectively, these are broadly: the regulatory requirements, for example, compliance with Part L2B Building Regulations in the United Kingdom; the static performance gap is a snapshot in time at a specific point, for example, when the building is first occupied and compared with designer's assumptions or models; the dynamic performance gap assumes a fluid and flexible changing of the space organically throughout time, for example, different types of building user or tenants. Imam et al (2017) recently investigated the internal "mental models"-the psychological representation of a real or imagined system (Craik, 1943)-of 108 thermal modellers and found a wide variability in their approaches to model inputs and ranking input parameters. Their findings include the observation that a quarter of modellers participating were making worse judgements than a random response and even the most experienced modellers, including external consultants, contributed great diversity (including some of the worst performance) to the overall results (Imam et al, 2017).…”
Section: Performance Gapmentioning
confidence: 99%
See 1 more Smart Citation
“…However, optimistic assumptions are often made in the design phase and semi-stationary calculation methodologies are still commonly employed [7]. Further, the gap between simulated and measured performance is a general issue [8] and the benefits of "green" design practices should be critically evaluated [9,10],…”
Section: Introductionmentioning
confidence: 99%
“…', 1 particularly the negative impression of building physics modelling introduced to the public domain.…”
mentioning
confidence: 99%